Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/bit.25604
|View full text |Cite
|
Sign up to set email alerts
|

Condensed lignin structures and re‐localization achieved at high severities in autohydrolysis of Eucalyptus globulus wood and their relationship with cellulose accessibility

Abstract: Eucalyptus globulus wood was subjected to autohydrolysis pretreatment at different severity factors. The pretreated materials were enzymatically saccharified at a substrate load of 10% (w/v) using a cellulase enzyme complex. Around 82-95% of original glucans were retained in the pretreated material, and the enzymatic hydrolysis yields ranged from 58% to 90%. The chemical and structural changes in the pretreated materials were investigated by microscopic (SEM, LSCM) and spectroscopic (2D-HSQC NMR and FT-IR) tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 37 publications
9
40
0
Order By: Relevance
“…Qualitatively, it is observed that the fluorescence of lignin droplets is stronger than that of the lignin in the fibers, thereby indicating that the concentration of lignin is greater in the droplets. Furthermore, the migration and relocation of the lignin component improved the enzymatic hydrolysis of the pretreated material obtained by the OSP3 condition, results that are in agreement with those previously published (Araya et al, 2015). These observations may be associated with the increase in the pore volume of the material (Donohoe et al, 2008), possible modifications of the crystallinity of the cellulose due to the reaction mechanism of the pretreatment (Hallac et al, 2010;Koo et al, 2012;Park et al, 2010;Sannigrahi et al, 2010a) and alteration to the degree of polymerization, which enhances enzyme digestibility (Hallac et al, 2010) by increasing the number of cellulose chain reducing ends, making it more reactive to enzymatic attack (Zhang and Lynd, 2004).…”
Section: Surface Morphology and Lignin Distributionsupporting
confidence: 93%
See 1 more Smart Citation
“…Qualitatively, it is observed that the fluorescence of lignin droplets is stronger than that of the lignin in the fibers, thereby indicating that the concentration of lignin is greater in the droplets. Furthermore, the migration and relocation of the lignin component improved the enzymatic hydrolysis of the pretreated material obtained by the OSP3 condition, results that are in agreement with those previously published (Araya et al, 2015). These observations may be associated with the increase in the pore volume of the material (Donohoe et al, 2008), possible modifications of the crystallinity of the cellulose due to the reaction mechanism of the pretreatment (Hallac et al, 2010;Koo et al, 2012;Park et al, 2010;Sannigrahi et al, 2010a) and alteration to the degree of polymerization, which enhances enzyme digestibility (Hallac et al, 2010) by increasing the number of cellulose chain reducing ends, making it more reactive to enzymatic attack (Zhang and Lynd, 2004).…”
Section: Surface Morphology and Lignin Distributionsupporting
confidence: 93%
“…2(C)). These globular deposits are formed when temperatures above the range of the lignin phase transition are reached, leading to the coalescence of lignin into larger molten bodies that migrate within and out the cell wall (Araya et al, 2015;Donohoe et al, 2008;Selig et al, 2007). In this work, a clear influence of the H 2 SO 4 concentration during the organosolv pretreatment over the formation of the lignin droplets is observed, and so further studies to fully understand the mechanism of formation must be performed.…”
Section: Surface Morphology and Lignin Distributionmentioning
confidence: 85%
“…Moreover, results of the present study are consistent with previous studies published by our research group. Thus, it this form of lignin is identified as an important factor for the high conversion of cellulose to glucose, the heterogeneous redistribution of lignin, resulting in, a significant decrease in the recalcitrance of pretreated materials 22,34,35 . In the pretreatment, when hemicellulose is removed, the lignin is more exposed to changes that promote its redistribution in the form of micro-droplets, generating random areas on the fibers with lower lignin content.…”
Section: Confocal Laser Microscopy (Clm)mentioning
confidence: 99%
“…Moreover, several studies have shown that small spherical clusters of lignin and pseudo-lignin (from carbohydrate degradation) 19 were formed on the surface of the fiber at high severity pretreatment. These studies examined the role of pseudo lignin on enzymatic digestibility 7,[20][21][22] . An understanding of the effects of pretreatments on the raw material, pretreated material characteristics and barriers for enzymatic hydrolysis represented by lignin micro-droplets formation are essential for the development of economic and competitive processes for bioethanol production In this study, Eucalyptus globulus wood was pretreated by different methods.…”
Section: Introductionmentioning
confidence: 99%
“…The autohydrolysis process has been optimized for increasing the recovery of hemicellulose in the form of monomeric sugars (such as xylose, mannose and galactose) or the respective oligo-saccharides, as well as for improving the production of glucose in the subsequent enzymatic hydrolysis of the cellulosic fraction [107]. In addition to its application to traditional wood species, such as eucalyptus [108], or fast-growing energy crops, such as Paulownia [109], autohydrolysis has been successfully employed for the valorization of the hemicellulosic content of vegetal byproducts or waste materials, such as barley straw [110], rapeseed cake [111], vine shoots [112] and invasive species such as gorse [113]. The development of kinetic models has provided fundamental understanding for the identification and evaluation of the most appropriate conditions for optimal autohydrolysis processes [114].…”
Section: Pretreatment Of Lignocellulosic Biomass For Hemicellulose Vamentioning
confidence: 99%